Economic efficiency during the transition - Goncharuk, Anatoliy G. (Naše gospodarstvo, 2006)
In spite of the fact that a market economy by definition must be more effective than a centrally planned economy, the various countries in transition from the latter to the former are faced with the problem of declining economic efficiency. In this paper a comprehensive index of economic efficiency is developed with the application of production function tools. The dynamics of economic efficiency of the economy of Ukraine, which met with one of the most pervasive transformational economic crises, are estimated and analyzed. It is shown that after a high rate of economic growth occurred in the Ukrainian economy in recent years, the level of efficiency of the economy remained quite low and even declined. This is explained by ineffective investments and innovations as well as an increasing intensity in use of materials.
Keywords: tranzicija; podjetja; produktivnost; efficiency; učinkovitost; inovacije; investicije; Ukraine; Ukrajina